Evaluation of EGFR inhibitor-mediated acneiform skin toxicity within the double-blind randomized EVITA trial: A thorough gender-specific analysis using the WoMo score - Gaiser, Maria; Lorenzen, Sylvie; Merx, Kirsten; Trojan, Jörg; Ocvirk, Janja; Ettrich, Thomas J.; Batran, Salah-Eddin al-; Schulz, Holger; Homann, Nils; Feustel, Hans-Peter; Schatz, Michael; Kripp, Melanie; et al. (Retrospektive Datenauswertung des Tumorregisters Würzburg im Zeitraum 2005 – 2013 bei Patienten mit Nicht-Kleinzelligem-Bronchialkarzinom (NSCLC) mit besonderer Betrachtung der Tyrosinkinaseinhibitor-Therapie bei EGFR-Mutation, 2019)
Acne-like skin reactions frequently occur in patients undergoing treatment with drugs inhibiting the epidermal growth factor receptor. Recently, the effects of vitamin K1 containing cream (Reconval K1) as prophylactic skin treatment in addition to doxycycline were explored in a double-blind randomized phase II trial (EVITA) in patients with metastatic colorectal cancer receiving cetuximab. EVITA demonstrated a trend towards less severe skin rash in Reconval K1-treated patients using the tripartite WoMo skin reaction grading score as a thorough tool for quantification of drug related skin reactions. This gender-specific analysis of the EVITA trial evaluated the application of the WoMo score for assessment of epidermal growth factor receptor (EGFR)-related skin toxicities according to treatment arm and gender. To show the robustness of results parametric and non-parametric statistical analyses were conducted. All three parts of the WoMo score independently demonstrated the superiority of the treatment arm (Reconval K1) regarding a significant reduction in acneiform skin reactions in women. Men did not benefit from Reconval K1 cream at any time point in none of the WoMo score analyses. The treatment effect in women was confirmed by the use of skin rash categories based on the final WoMo overall score and mixed effect longitudinal multiple linear regression analysis. The WoMo score represents a sensitive tool for studies exploiting treatments against EGFR mediated acne-like skin rash. Part C of the WoMo score seems to be sufficient for quantification of drug related skin toxicities in further studies. Standard WoMo skin reaction score values for future studies are provided.
First published: 14 June 2019
Gesehen am 19.05.2020